Transformasi Tata Kelola Masyarakat Adat: Ketahanan Komunitas dalam Menghadapi MIFEE dan Kebijakan Konservasi di Merauke - Pecamuya, Robertus (INDO PUBLISHING, 2025)
This study aims to analyze the transformation of indigenous peoples' governance in facing the Merauke Integrated Food and Energy Estate (MIFEE) and conservation policies, identify community resilience strategies as adaptations to these policies, and provide relevant policy recommendations for sustainable development based on local wisdom. A qualitative approach with a case study design was used to explore local dynamics in Jagebob District, Merauke Regency, South Papua. Data were collected through in-depth interviews with 18 key informants, participant observation, and document studies, then analyzed using thematic analysis techniques. The results showed that indigenous peoples experienced significant transformations in governance, characterized by strengthening customary institutions, revitalizing community deliberations, and integrating traditional values ​​with modern governance practices. Community resilience strategies include livelihood diversification, policy advocacy, and strengthening cultural identity as a form of adaptation and non-violent resistance. Supporting factors include the role of customary leaders, the younger generation, NGOs, and technology; while obstacles include power imbalances, weak law enforcement, and community fragmentation. These findings underscore the urgency of more inclusive development and conservation policies, recognizing indigenous governance as an equal partner, and strengthening local institutional capacity to support sustainable development.